2015
DOI: 10.1038/srep15957
|View full text |Cite
|
Sign up to set email alerts
|

Compressible and monolithic microporous polymer sponges prepared via one-pot synthesis

Abstract: Compressible and monolithic microporous polymers (MPs) are reported. MPs were prepared as monoliths via a Sonogashira–Hagihara coupling reaction of 1,3,5-triethynylbenzene (TEB) with the bis(bromothiophene) monomer (PBT-Br). The polymers were reversibly compressible, and were easily cut into any form using a knife. Microscopy studies on the MPs revealed that the polymers had tubular microstructures, resembling those often found in marine sponges. Under compression, elastic buckling of the tube bundles was obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 47 publications
(54 reference statements)
1
33
0
Order By: Relevance
“…5 and using the above mentioned equation. The obtained Young’s modulus signifies significant elastic behavior compared with that reported for similar compressible foams 30 , 31 . Compression can be done up to 76% of its original volume because it regains its original shape within 30 s after release.…”
Section: Resultssupporting
confidence: 55%
“…5 and using the above mentioned equation. The obtained Young’s modulus signifies significant elastic behavior compared with that reported for similar compressible foams 30 , 31 . Compression can be done up to 76% of its original volume because it regains its original shape within 30 s after release.…”
Section: Resultssupporting
confidence: 55%
“…The network structure of spongin fibers determines one of the most attractive features of commercial sponges—their compressibility [ 89 ]. A simple test demonstrating the resistance to strain under pressure and the flexibility of a commercial bath sponge of the species H. communis is presented in Figure 10 .…”
Section: Materials Properties Of 3d Spongin Scaffoldsmentioning
confidence: 99%
“…There have been a few reports on tubular or fibrillar cross‐linked polymers, but the mechanisms for their formation have not been fully understood. We previously reported that the Sonogashira–Hagihara coupling reaction of 1,3,5‐triethynylbenzene with the bis(bromothiophene) monomer produced a compressible monolith consisting of tubular polymer fibers . Our study suggested that tubular shapes were likely formed by step reactions in combination with structured self‐assembly of the reactants in the reaction mixture, such as monomers, linear oligomers, and branched polymers having reactive ethynyl groups.…”
Section: Resultsmentioning
confidence: 61%